The shear-lag effect of composite box girder bridges with corrugated steel webs and trusses. (15th February 2019) - Chen, Yiyan; Dong, Jucan; Xu, Tianhua; Xiao, Yufeng; Jiang, Ruijuan; Nie, Xinmin
Highlights: The shear-lag effect of CBGB-CSWTs are studied. The concrete filled in bottom steel tubes has little influence on the shear-lag effect. The width-to-span ratio is an important influencing factor of the shear-lag effect. Analytical equations are developed to calculate the shear-lag coefficient. Abstract: The composite box girder bridge with corrugated steel webs and trusses is a recently proposed enhanced composite box girder bridge structure. The shear-lag effect of this kind of structure is studied in detail in this research. Two 8.744 m-long test beams with and without concrete filled in the bottom steel tubes were constructed and tested. The non-uniform distribution of cross-sectional stress in the top concrete slab was captured. The filling of concrete inside the bottom steel tubes is shown not to have a great influence on the shear-lag effect. Numerical parametric studies were carried out to study the influence of various factors on the shear-lag effect of this kind of structure. The numerical results indicate that the magnitude of the shear-lag effect increases with the width-to-span ratio and the suspension ratio. Analytical equations were derived to calculate the shear-lag coefficient for composite box girders with corrugated steel webs and trusses based on the energy variational principle. The experimental and numerical validation indicates that the proposed equations can be well applied in engineering practice.